Training students majoring in disease prevention at a medical university - V. I. Starodubov; N. P. Soboleva; S. N. Alekseenko; K. G. Gurevich; E. D. Savchenko (Сеченовский вестник, 2016)
The article discusses the training of students at the department of disease prevention and healthy lifestyle at a medical university.